Reduced hospital revenue due to error code diagnosis in the implementation of INA-CBGs - Warsi Maryati; Novita Yuliani; Anton Susanto; Aris Octavian Wannay; Ani Ismayani Justika (International Journal of Public Health Science (IJPHS), 2021)
In the case-mix system, diagnostic codes are used as the basis for classifying health service rates. The difference in tariffs between hospitals and the accuracy of the diagnosis code causes a gap where there are hospitals that benefit and are disadvantaged by the Indonesian case-based groups (INA-CBGs) tariff policy. This study assesses the gap factor between hospital rates and INA-CBGs rates, which include hospital characteristics and the accuracy of the diagnosis code. Samples were taken of 100 medical record documents of inpatients at two hospitals in Surakarta, Central Java, Indonesia in 2020 by stratified random sampling. Data were collected by observation and analyzed by Chi-Square test. There were errors in the primary diagnosis code 11 (32.35%), secondary diagnosis code 19 (55.88%), combination diagnosis code 4 (11.76%). Changes in the INA-CBG code that caused the inaccuracy of the claim rate were 26 (59.09%) case-mix main groups (CMG) codes, 44 (100%) CBG-specific codes, 31 (70.45%) severity level codes. Public-private hospitals with class B experienced a decrease in income of IDR 46,081,900 (-17.50%), while special government hospitals with class A experienced an additional income of IDR 99,733,869 (38.31%). An accurate diagnostic code can increase the odds by 42.128 times the accuracy of the INA-CBGs rate (b=42.128; 95% CI=11.127 to 159.497; p<0.001).